Rapid alkaline methylene blue supravital staining for assessment of anterior segment infections - Kiuchi K (Dove Medical Press, 2016)
Katsuji Kiuchi Kiuchi Eye Clinic, Joto-ku, Osaka, Japan Purpose: To present the Löffler’s alkaline methylene blue technique of staining eye discharges in eyes with anterior segment infections.Method: The Löffler’s alkaline methylene blue staining method is a simple staining technique that can be used to differentiate bacterial, viral, and fungal infections. It is a cationic dye that stains cells blue because the positively charged dye is attracted to negatively charged particles such as polyphosphates, DNAs, and RNAs. Specimens collected from patients by swabbing are smeared onto microscope slides and the methylene blue solution is dropped on the slide. The slide is covered with a glass cover slip and examined under a microscope. The entire time from the collection to the viewing is about 30 seconds.Results: Histopathological images of the conjunctival epithelial cells and neutrophils in eye discharges were dyed blue and the nuclei were stained more intensely blue. Bacterial infections consisted mainly of neutrophils, and viral infections consisted mainly of lymphocytes.Conclusions: Löffler’s alkaline methylene blue staining can be done in about 30 seconds for diagnosis. Even though this is a one color stain, it is possible to infer the cause of the infection by detection of the absence of bacteria and/or fungi in context of the differential distribution of neutrophils and lymphocytes. Keywords: alkaline methylene blue, supravital staining, discharge, anterior segment infections